Effect of the Performance of Lignin Into the Matrix of the TiO2 with Application on DSSCs - Edwalder Silva Teixeira; Vanja Fontenele Nunes; Diego Caitano Pinho; Paulo Herbet França Maia Júnior; Francisco Marcone Lima; Men de Sá Moreira de Souza Filho; Ana Fabíola Leite Almeida; Francisco Nivaldo Aguiar Freire (Floresta e Ambiente, 2022)
Abstract Founding new materials and structures for solar cells is a challenge in the photovoltaic field. This work evaluated the effect of the lignin in the photovoltaic activity by compounding with TiO2/lignin as photoanode for the dye sensitized solar cells (DSSC’s). Hybrid films (TiO2/lignin) with different concentrations of lignin (5, 10 and 15%) were deposited by spin coating over commercial TiO2 thin films. The cells were sandwich assembled. The characterizations were done through analysis of absorbance, band gap, x-ray diffraction, morphological and electrical. The lignin at 15% reduced the TiO2 band gap from 3.66 to 2.84 eV, favoring the short current density to 11.06 mA/cm2 and efficiency of 4.65%, an increase of 103.95% compared to the TiO2 structure without lignin.